Using Seawater Reverse Osmosis (SWRO) Technology in Seawater Desalination Processes - Hapsari, Larasati Putri; Pranoto, Aris Kabul; Rinjani, Widi Ayu; Anasri, Anasri; Anjani, Ika; Rahman, Abdul (Politeknik Kelautan dan Perikanan Karawang, 2022)
Water is one of the basic needs for human life, including for people living on the coast. It is difficult to get clean water for consumption because most coastal areas are affected by sea conditions that have high salinity. In order to be consumed, the saline water must be desalinated. Desalination is a process to convert saline water into fresh water. One such desalination technology is using reverse osmosis (RO). The purpose of this study was to determine the process of desalination of seawater into freshwater using the seawater reverse osmosis (SWRO) method. The method used in this research is observation, which is to see directly the stages of the desalination process of seawater into fresh water. The data was obtained in the form of primary data from observations and secondary data from the literature to support primary data. Analysis of the data used in the form of descriptive analysis by describing each stage carried out in the SWRO process. The results showed that the seawater desalination process using SWRO technology had 14 stages. These stages include; intake, raw water pump, raw water reservoir, UF feed pump, Automatic screen, ultrafiltration, UF water reservoir, RO feed pump, HPP & booster, RO membrane, RO water reservoir, permeate pump, chlorine analyzer, product water. In developed and developing countries, SWRO units have been widely used, because by processing seawater into freshwater, there are many benefits for the life cycle and it is environmentally friendly. It also maintains underground fresh water so that it can provide plant life, and trees that provide us with clean oxygen for our lives.